Using an android devices as mobile extensible HMIs - Cheypoca, Thepjit; Anuntahirunrat, Kongsuk (My University, 2020)
In this paper, an android application monitoring and control with programmable logic controller (PLC) system is proposed, which helps the production engineer self-correct the system without restriction of time and place. The proposed android application consists of smart phone, access point and PLC Siemens S7-1200. The feasibility of this method is illustrated by experimental using different parameter databases. Recognition results show this approach is efficient.
Keywords: Android application; Programmable logic controller; TIA Portal